Giant Ovarian Cyst: A Case Report from A Post Menopausal Woman - Pramana, Cipta; Kurnia Tandi , Joshua; Dian Lestari , Novi (International Journal of Psychosocial Rehabilitation, 2020)
Background: Giant ovarian cyst is one type of ovarian tumor which is rarely found at this time. The level of awareness of patients to examine their health conditions has a great influence in decreasing this case. Case: We report a 62-year-old woman with a giant ovarian cyst with cyst size of 22.13 cm x 28.28 cm x 30.48 cm. Laparotomy cystectomy, sinusalpingo-oophorectomy, adhesiolysis, and omentectomy were performed to the patient, considering the possibility of malignancy. Result: The results of the cyst decompression with controlled drainage are as much as 6 liters of liquid, with a total tissue weight of 1 kg. Histopathology examination of cystic tissue I suggest a malignant sex-cord-stromal tumor with endometriosis cysts, cyst tissue II suggests a malignant sex cord-stromal tumor with endometriosis cysts and an unclassified sex cord tumor, and the left tubal tissue suggests hydrosalpinx. Histopathology examination of the omentum suggests a malignant ovarian tumor metastasis. Hysterectomy was not performed on this patient because the clinician have not been able to determine whether this cyst is a malignancy or not. Conclusion: Post-operative patient condition is well monitored and can go home on the 3rd post-operative day. After we receive the histopathology examination result, the patient was referred to a tertiary type hospital for further diagnosis and management.